2017
DOI: 10.1080/21505594.2017.1326438
|View full text |Cite
|
Sign up to set email alerts
|

S. oralis activates the Efg1 filamentation pathway in C. albicans to promote cross-kingdom interactions and mucosal biofilms

Abstract: Candida albicans and Streptococcus oralis are ubiquitous oral commensal organisms. Under hostpermissive conditions these organisms can form hypervirulent mucosal biofilms. C. albicans biofilm formation is controlled by 6 master transcriptional regulators: Bcr1, Brg1, Efg1, Tec1, Ndt80, and Rob1. The objective of this work was to test whether any of these regulators play a role in crosskingdom interactions between C. albicans and S. oralis in oral mucosal biofilms, and identify downstream target gene(s) that pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 52 publications
7
62
0
1
Order By: Relevance
“…Previous studies showed that C. albicans and S. oralis have a mutualistic relationship in the biofilm growth state which promotes fungal virulence [22,23]. In this work we showed that gtfR promotes sessile growth of S. oralis on all tested surfaces in vitro and in vivo, when sucrose is available.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…Previous studies showed that C. albicans and S. oralis have a mutualistic relationship in the biofilm growth state which promotes fungal virulence [22,23]. In this work we showed that gtfR promotes sessile growth of S. oralis on all tested surfaces in vitro and in vivo, when sucrose is available.…”
Section: Discussionsupporting
confidence: 58%
“…Biofilms of streptococci and C. albicans were allowed to develop for 6-48 h in RPMI 1640 medium supplemented with 10% FBS and 10% BHI [22,23]. In 48 h biofilms, fresh media were added after 24 h. In some experiments media were supplemented with 1-5% [wt/vol] sucrose or 1% glucose [24].…”
Section: Single and Mixed Biofilm Growth On Abiotic Surfacesmentioning
confidence: 99%
See 3 more Smart Citations